Can high‐temperature, high‐heat flux hydrothermal vent fields be explained by thermal convection in the lower crust along fast‐spreading Mid‐Ocean Ridges?. (10th May 2017) - Fontaine, Fabrice J.; Rabinowicz, M.; Cannat, M.
Abstract: We present numerical models to explore possible couplings along the axis of fast‐spreading ridges, between hydrothermal convection in the upper crust and magmatic flow in the lower crust. In an end‐member category of models corresponding to effective viscosities μM lower than 10 13 Pa.s in a melt‐rich lower crustal along‐axis corridor and permeability k not exceeding ∼10 −16 m 2 in the upper crust, the hot, melt‐rich, gabbroic lower crust convects as a viscous fluid, with convection rolls parallel to the ridge axis. In these models, we show that the magmatic‐hydrothermal interface settles at realistic depths for fast ridges, i.e., 1–2 km below seafloor. Convection cells in both horizons are strongly coupled and kilometer‐wide hydrothermal upflows/plumes, spaced by 8–10 km, arise on top of the magmatic upflows. Such magmatic‐hydrothermal convective couplings may explain the distribution of vent fields along the East (EPR) and South‐East Pacific Rise (SEPR). The lower crustal plumes deliver melt locally at the top of the magmatic horizon possibly explaining the observed distribution of melt‐rich regions/pockets in the axial melt lenses of EPR and SEPR. Crystallization of this melt provides the necessary latent heat to sustain permanent ∼100 MW vents fields. Our models also contribute to current discussions on how the lower crust forms at fast ridges: they provide a possible mechanism for focused transport of melt‐rich crystal mushes from moho level to the axial melt lens where they further crystallize, feed eruptions, and are transported both along and off‐axis to produce the lower crust. Key Points: The gabbroic magma chamber in the lower crust along the axis of fast MOR can convect as a viscous fluid Magmatic convection controls the distribution of hydrothermal fields and the pattern of melt delivery in the AML along fast MOR Lower crust convection offers new perspectives on the formation of the lower crust of fast MOR